6p+4.7=13.5p

Simple and best practice solution for 6p+4.7=13.5p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p+4.7=13.5p equation:


Simplifying
6p + 4.7 = 13.5p

Reorder the terms:
4.7 + 6p = 13.5p

Solving
4.7 + 6p = 13.5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-13.5p' to each side of the equation.
4.7 + 6p + -13.5p = 13.5p + -13.5p

Combine like terms: 6p + -13.5p = -7.5p
4.7 + -7.5p = 13.5p + -13.5p

Combine like terms: 13.5p + -13.5p = 0.0
4.7 + -7.5p = 0.0

Add '-4.7' to each side of the equation.
4.7 + -4.7 + -7.5p = 0.0 + -4.7

Combine like terms: 4.7 + -4.7 = 0.0
0.0 + -7.5p = 0.0 + -4.7
-7.5p = 0.0 + -4.7

Combine like terms: 0.0 + -4.7 = -4.7
-7.5p = -4.7

Divide each side by '-7.5'.
p = 0.6266666667

Simplifying
p = 0.6266666667

See similar equations:

| 6x+24=16x-6 | | 3(c-4)+3=2+c-11 | | 12-7=140-35x | | -2u-2=-9u+5 | | 21*10/3 | | (3x-8)(8x+7)= | | 4a-13=-8 | | 1/4(y+4)=3 | | 11x+22=5x+184 | | 1.4u-1.2=0.1u-5.1 | | 3(4x-10)=6x-60 | | 3(x-2)+2(x+5)=2[x+(2x-1)] | | 9x+13=6x+2 | | -1/8(z-6)=-3/4(z-1/9) | | -1/2(z+1/9)=-3/8(z+1/2) | | 3+6n=7n-5 | | g(x)=x^2-2x-5 | | 1000+700+6x=800+300+8x | | 117-7x=29x+17 | | 7y+21=5 | | -2w-17=4w+19 | | 2/12+3/4 | | 8(2x+5)=3(x+4)+2 | | 7x-2(5-x)=3+2x+1 | | 5*12+13+3*14+2*15+4*16+17+19+3*20/20 | | 12-8m=2m+2 | | 14-(2q+5)=(-2q)+9 | | -3/4x+5/4=x+3 | | 12x+4/4(x-1)(x+1)=5/4 | | 8x-16=4(2x-4) | | 22=4+3t | | x+30=93 |

Equations solver categories